(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Lifestyle factors affect female consumers' satisfaction with facial mask usage. As modern life accelerates and stress levels rise, women's demand for high quality and convenient skincare products grows. Facial masks, as a key component of daily skincare routines, are subject to variations in satisfaction levels depending on individual characteristics and lifestyle patterns. This research employed purposive sampling and conducted a questionnaire survey targeting Taiwanese women with prior experience using facial masks. The results indicate that certain demographic variables such as marital status, age, and educational level significantly affect satisfaction with facial masks. Specifically, unmarried women and those with a university education reported higher satisfaction with the efficacy of facial masks. Self-image, brand orientation, and trend consciousness were analyzed regarding lifestyle dimensions. Except for trend consciousness, the other two lifestyle dimensions showed a significant positive correlation with satisfaction regarding product design and functional performance. Respondents strongly emphasized self-image and demonstrated the highest level of satisfaction with the product's appearance and effectiveness.